An Experimental Assessment of the Public’s Views on Immigration When the Terms Illegal and Undocumented are Juxtaposed - Chenane, Joselyne L. (Crime & delinquency, 2024)
The twin topics of immigrants and immigration have been known to generate strong debates within the American body politic due to these debates? reverberations in U.S. society. Immigration has remained a contentious policy issue for several decades because of Americans? divergent opinions about opening the nation?s borders to immigrants. Using YouGov data, we show that employing the terms illegal immigrant and undocumented immigrant produced different reactions among the survey participants. We also show, via multivariate analyses, that participants who voted for Donald Trump, those who did not vote in the 2016 Presidential election, and conservatives were more likely than liberals and those who voted for Hillary Clinton to endorse Immigration and Customs Enforcement?s (ICE) twin policies of separating immigrant parents from their children at the U.S.-Mexico border and arresting illegal immigrants who have overstayed their visas, even if they have not committed a crime. The implications of our findings for policy, group relations, and future research are discussed.